Flood Scenario of Tigris River in Baghdad City - Shaban, Auday H. (Iraqi Journal of Science, 2023)
Flooding hazard is an important and dangerous natural phenomenon that leads to significant material losses. It should be studied and scenario to prevent significant losses. The studies should consider the impact of many factors such as human, infrastructure, economic,..etc. The main objective of the research is the risk management procedure. The study was conducted in Baghdad, Iraq. The materials for completing this research were prepared by gathering a satellite image and Digital Elevation Model (DEM) via the USGS website, then processed, analyzed, and converted into a different flood region concerning the probability of rising water levels where the normal height of Baghdad city is 28m over sea level. This scenario defines 3m, 4m, and 5m heights over the Tigris river cliff, which are the possible heights at which the water level may rise above the normal height. The range of the elevations becomes either 31m, 32m, or 33m over sea level. Many software’s were conducted in this research, such as MatLab, ArcGIS, and ENVI.